2001
DOI: 10.1093/ndt/16.9.1870
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer hydrochloride (Renagel®), a non‐calcaemic phosphate binder, arrests parathyroid gland hyperplasia in rats with progressive chronic renal insufficiency

Abstract: Sevelamer treatment arrested hyperphosphataemia and PTG hyperplasia accompanied by the elevation of serum PTH levels. The correlation analysis suggests that reduced serum phosphorus levels contributed to the suppression of PTG hyperplasia and resulted in the reduction of PTH levels in this animal model after the sevelamer treatment. The management of phosphorus control started from early stage of CRI could prevent PTG hyperplasia and facilitate later management of secondary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
4
26
2
Order By: Relevance
“…A study conducted by Nagano et al, (2001) on male Sprague-Dawley rats, stated a higher control concentration of 1,25(OH)2D3 (54.7±3.28 pg/ml) than the present study (23.6±4.5pg/ml).…”
Section: Discussioncontrasting
confidence: 79%
“…A study conducted by Nagano et al, (2001) on male Sprague-Dawley rats, stated a higher control concentration of 1,25(OH)2D3 (54.7±3.28 pg/ml) than the present study (23.6±4.5pg/ml).…”
Section: Discussioncontrasting
confidence: 79%
“…It has been reported that increased blood urea nitrogen (BUN) and serum creatinine levels, decreased creatine clearance in doxorubicin treated Sprague-Dawley rats compared to the control [23]. Another study has indicated significant serum creatine, uric acid and BUN increase in doxorubicin-treated rats compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the Size of the Rat PTG Serial sections of the paraffin-embedded rat PTGs were cut (4 m) and stained with H&E. The maximal two-dimensional area of the right or left PTG was determined from at least ten serial sections according to the method described by Nagano et al 57 The sections were examined under a light microscope (Olympus CX40) connected to a computer. A digitizer tablet carefully traced the outside edge of the PTG, and the area inside of the circle was calculated by an image analysis system (Image J).…”
Section: Histologic Studiesmentioning
confidence: 99%